Novel swelling adhesive tape for lithium battery and preparation method of novel swelling adhesive tape
By synthesizing porous carbon and reinforced fillers in the expanded substrate of the swelling tape for lithium batteries, the problems of limited swelling ratio of the base material and the expansion substrate affecting lithium ion transmission are solved, and efficient lithium ion transmission and electrochemical performance are achieved. .
Patent Information
- Application Number
- CN202411415336.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-02-25
AI Technical Summary
The base material of the swelling tape for lithium batteries has limited swelling ratio in the thickness direction, and cannot effectively fill the gap between the lithium battery cell and the cylindrical shell, and the expansion substrate is coated on the lithium-ion battery electrode sheet to affect the transmission efficiency of lithium ions. .
The titanium carbide nanosheets are modified by oxalic acid surface and mixed with the organic precursor and calcined at high temperature to synthesize porous carbon, enhancing the ion storage capacity and transmission channels of the expanded substrate. At the same time, glucopolyphenol reacts with trimethylhexamethylene diisocyanate and mixed with composite titanium carbide nanosheets to increase adhesion and cross-linking density.
It improves the transmission efficiency of lithium ions, enhances the mechanical properties and compressive resistance of the expanded substrate, ensures the electrochemical performance of the lithium ion battery, and effectively fills the gap of the lithium battery.
Smart Images

Figure BDA0005079274950000151
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of swelling tapes, in particular to a novel swelling tape for lithium batteries and a preparation method thereof. Background Art
[0002] With the rapid development of new energy vehicles and energy storage industries, the development of the lithium battery industry has received more and more attention and importance, and the research and development and improvement of related materials have gradually become a hot topic in the field of scientific research; swelling tape, as an important product widely used in the lithium battery industry, has received high attention. After the swelling tape is immersed in the electrolyte, it will expand in volume and fill the gap between the lithium battery cell and the shell, so that the shell and the inner core of the lithium battery are connected as one. In this way, when the lithium battery encounters vibration, the relative movement of the cell and the steel shell can be avoided, preventing battery short circuit, lug desoldering and other phenomena, ensuring battery safety and extending battery life.
[0003] At present, the base materials used in the swelling tape for lithium batteries mostly swell in the thickness direction, and the swelling ratio in the thickness direction is limited, and the gap between the lithium battery cell and the cylindrical shell cannot be effectively filled; the expansion substrate with polar side groups such as ester, carboxyl, and hydroxyl groups is coated on the lithium-ion battery pole piece, which improves the polarity of the molecular structure and improves its swelling performance in polar solvents, but the expansion substrate coated on the lithium-ion battery pole piece affects the transmission efficiency of lithium ions, thereby not affecting the electrochemical performance of the lithium-ion battery; by incorporating layered nanosheets in the expansion substrate, the transmission efficiency of lithium ions can be effectively improved, but the dispersion of the layered nanosheets in the substrate is poor, and the mechanical properties of the expansion substrate need to be improved. Summary of the invention
[0004] The purpose of the present invention is to provide a novel swelling tape for lithium batteries and a preparation method thereof: titanium carbide nanosheets are surface-modified with oxalic acid, then mixed with an organic precursor, calcined at high temperature, and porous carbon is synthesized on the surface of the titanium carbide nanosheets. The synthesized porous carbon provides more ion storage capacity and transmission channels, so that the expanded substrate is coated on the lithium ion battery pole piece, and has a higher lithium ion transmission efficiency, thereby not affecting the electrochemical performance of the lithium ion battery; the grape polyphenol used in the reinforcing filler of the substrate reacts with trimethyl hexamethylene diisocyanate, and then mixed with the composite titanium carbide nanosheets. The grape polyphenol and trimethyl hexamethylene diisocyanate are combined with an amide bond, which increases the adhesion performance with the pole piece. The composite is grafted on the surface of the composite titanium carbide nanosheet and can be bonded to the pole piece. The carboxyl and hydroxyl groups in the polar expansion substrate undergo cross-linking reaction, so that the transmission efficiency of the lithium ion battery and the electrochemical performance are improved in the composite titanium carbide nanosheet polar expansion substrate; the surface of the nano calcium carbonate is modified with betaine, and then it is mixed with acrylamide and methacryloylethyl sulfobetaine, stirred and reacted to form a flexible hydrogel, which is filled into the pressure-sensitive adhesive and used as a pressure-sensitive layer to improve the flexibility of the swelling tape, and improve the dispersibility of the calcium carbonate powder in the pressure-sensitive adhesive system, and promote the compactness of the acrylic pressure-sensitive adhesive; the release layer raw materials are mixed, and the release layer mixture is coated on the upper surface of the expansion substrate with the pressure-sensitive adhesive layer, heated and cured, and rolled up, which can reduce the unwinding force of the finished tape and can also make the tape flat and rolled up during production to avoid wrinkles.
[0005] The technical problems to be solved by the present invention are as follows: the base materials used in the swelling tape for lithium batteries mostly swell in the thickness direction, and the swelling ratio in the thickness direction is limited, which cannot effectively fill the gap between the lithium battery cell and the cylindrical shell, and the swelling substrate coated on the lithium-ion battery electrode affects the transmission efficiency of lithium ions, thereby not affecting the electrochemical properties of the lithium-ion battery; the layered nanosheets have poor dispersion in the substrate, and the mechanical properties of the swelling substrate need to be improved.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A method for preparing a novel swelling tape for lithium batteries comprises the following steps:
[0008] S1. Melt and blend the substrate raw materials, and then photo-curing them by ultraviolet light irradiation to obtain an expanded substrate.
[0009] S2. Mix the raw materials for the pressure-sensitive adhesive layer, apply them on the lower surface of the expansion substrate, and heat-cure to obtain an expansion substrate with a pressure-sensitive adhesive layer.
[0010] S3. Mix the release layer raw materials, apply the release layer mixture on the upper surface of the expansion substrate with the pressure-sensitive adhesive layer, heat and cure, and roll up to obtain an expansion substrate with a release layer and a pressure-sensitive adhesive layer, that is, a new swelling tape for lithium batteries.
[0011] Furthermore, in step S1, the ultraviolet light irradiation power is 200-300W, the wavelength is 200-300nm, the temperature is 20-30°C, and the irradiation time is 10-15min.
[0012] Furthermore, in step S2, the thermal curing temperature is 105-120°C, and the thermal curing time is 2-3 minutes.
[0013] Furthermore, in step S3, the heating curing temperature is 130-150° C., and the heating curing time is 1-2 min.
[0014] Furthermore, the novel swelling tape for lithium batteries includes a pressure-sensitive adhesive layer, an expansion substrate layer, and a release layer from the inside to the outside; the thickness of the pressure-sensitive adhesive layer is 6-10um, the thickness of the expansion substrate layer is 40-50um, and the thickness of the release layer is 1-2um.
[0015] Furthermore, the weight percentages of the substrate raw materials are as follows: 40-70 parts of polyurethane resin, 30-60 parts of modified acrylate monomers, 5-6 parts of reinforcing fillers, and 0.1-1 parts of photoinitiators.
[0016] Furthermore, the polyurethane resin is selected from polyurethane acrylate oligomers or aromatic polyurethane acrylate oligomers.
[0017] Furthermore, the photoinitiator is selected from any one of (2,4,6-trimethylbenzoyl)diphenylphosphine oxide, 1-hydroxycyclohexyl phenyl ketone, and 2-hydroxy-2-methyl-1-phenyl-1-propanone.
[0018] Furthermore, the reinforcing filler is prepared by reacting grape polyphenol with trimethyl hexamethylene diisocyanate and then mixing with composite titanium carbide nanosheets. Specifically, the reinforcing filler is prepared by the following steps:
[0019] Add grape polyphenol and trimethyl hexamethylene diisocyanate to dimethyl sulfoxide, stir evenly, add triethylamine, stir at 60°C for 30 minutes, add composite titanium carbide nanosheets, stir and react for 10 minutes, filter, wash with deionized water 3 times, and dry in an oven at 70°C for 10 minutes to obtain a reinforced filler.
[0020] Among them, in the organic solvent dimethyl sulfoxide, triethylamine is used as a catalyst to enable the hydroxyl groups in the polyphenol to react with the isocyanate of trimethylhexamethylene diisocyanate and combine with amide bonds. The formed complex contains hydroxyl groups, isocyanate groups and amide bonds, which can be combined with the composite titanium carbide nanosheets through chemical bonds, so that the complex is grafted on the surface of the composite titanium carbide nanosheets. The hydroxyl groups and isocyanate groups carried by the complex can undergo cross-linking reactions with the carboxyl groups and hydroxyl groups in the expanded substrate of the three-dimensional network structure, so that the composite titanium carbide nanosheets are filled into the expanded substrate of the three-dimensional network structure.
[0021] Furthermore, the usage ratio of grape polyphenol, trimethylhexamethylene diisocyanate, dimethyl sulfoxide, triethylamine, and composite titanium carbide nanosheets is (2-3) g: (1-2) g: (10-20) mL: (0.01-0.03) g: (0.3-0.7) g.
[0022] Furthermore, the composite titanium carbide nanosheets are prepared by modifying the titanium carbide nanosheets on the surface with oxalic acid, mixing with an organic precursor, and calcining at a high temperature.
[0023] Furthermore, the organic precursor is one of glucose, rice husk powder, starch, and sugarcane bagasse.
[0024] Furthermore, the high temperature calcination temperature is 800-900°C, and the high temperature calcination time is 2-5h.
[0025] Furthermore, the titanium carbide nanosheets have a diameter of 0.1-1 μm and a thickness of 20-40 nm.
[0026] Furthermore, the composite titanium carbide nanosheets are prepared by specifically comprising the following steps:
[0027] Add titanium carbide nanosheets and organic precursors to deionized water, stir evenly, add oxalic acid and 36% hydrochloric acid by mass, stir and react at 70°C for 30 minutes, filter, wash and dry, place in a tube furnace, add potassium hydroxide, activate at 400°C for 1 hour, introduce nitrogen, calcine at 850°C for 3.5 hours, cool to room temperature, take out, wash 3 times with deionized water, and dry in an oven at 70°C for 10 minutes to obtain composite titanium carbide nanosheets.
[0028] Among them, the carboxyl group of oxalic acid can be combined with the hydroxyl group on the surface of titanium carbide nanosheets through chemical bonds, so that oxalic acid is coated on the surface of titanium carbide nanosheets, giving active functional groups carboxyl groups, and the carboxyl groups contained in the titanium carbide nanosheets coated with oxalic acid can be combined with the oxygen-containing functional groups of the organic precursor through chemical bonds, so that the organic precursor is coated on the surface of the titanium carbide nanosheets.
[0029] Furthermore, after high-temperature calcination, the organic precursor glucose is thermally decomposed to form a dense carbon layer, and the activator potassium hydroxide molecules are decomposed to form pores on the surface of the dense carbon layer, thereby realizing the synthesis of porous carbon on the surface of titanium carbide nanosheets. The synthesized porous carbon provides more ion storage capacity and transmission channels, so that the expanded substrate is coated on the lithium-ion battery electrode, which has a higher lithium ion transmission efficiency and does not affect the electrochemical performance of the lithium-ion battery.
[0030] Furthermore, the dosage ratio of titanium carbide nanosheets, organic precursor, deionized water, oxalic acid, and potassium hydroxide is (0.1-0.3) g: (3-7) g: (40-60) mL: (5-5.4) g: (3-7) mL.
[0031] Furthermore, the modified acrylic ester monomer is prepared by reacting dextran with an acrylic ester monomer.
[0032] Furthermore, the acrylic acid ester monomer is selected from any one of hydroxyethyl methacrylate, hydroxyethyl acrylate and acrylic acid.
[0033] Furthermore, the modified acrylic ester monomer is prepared by specifically comprising the following steps:
[0034] Add acrylate monomer and dextran to ethanol, stir evenly, place in a 50°C water bath, add 36% by mass hydrochloric acid aqueous solution, stir and react for 30 minutes, take out, cool to room temperature, stand for 2 hours, remove the upper ethanol solution, remove the reactant, place in a 60°C oven and dry for 10 minutes, grind into powder to obtain a modified acrylate monomer.
[0035] Among them, in the organic solvent ethanol, hydrochloric acid solution is used as a catalyst, and the hydroxyl groups contained in dextran can be combined with the oxygen-containing functional groups in the acrylate monomers through chemical bonds, so that the acrylate monomers are grafted on the dextran molecular chain, providing photopolymerizable monomers, so that the dextran is filled into the expansion substrate, and the dextran molecular chain contains a large number of polar functional groups such as hydroxyl groups and ester groups. The polar functional groups are easy to absorb the ester solvent in the electrolyte, so that it enters the expansion substrate in large quantities, and the substrate can expand at a higher rate.
[0036] Furthermore, the usage ratio of acrylic acid ester monomer, dextran, ethanol and hydrochloric acid aqueous solution is (1.2-1.4) g: (3-5) g: (40-60) mL: (0.3-0.7) mL.
[0037] Furthermore, the weight percentages of the raw materials for the pressure-sensitive adhesive layer are: 50-60 parts of acrylic acid, 10-15 parts of isooctyl acrylate, 6-10 parts of lauric methacrylate, 2-5 parts of composite hydrogel, 0.2-1 parts of curing agent, 0.1-0.5 parts of initiator, and 50-70 parts of toluene.
[0038] Furthermore, the curing agent is selected from toluene diisocyanate; and the initiator is selected from benzoyl peroxide or azobisisobutyronitrile.
[0039] Furthermore, the composite hydrogel is prepared by modifying the surface of nano calcium carbonate with betaine, and then mixing with acrylamide and methyl acryloylethyl sulfobetaine, and stirring for reaction.
[0040] Furthermore, the particle size of the nano calcium carbonate is 10-13 μm.
[0041] Furthermore, the composite hydrogel is specifically prepared by the following steps:
[0042] A1. Add betaine and nano-calcium carbonate to ethanol, stir at 40°C for 30 minutes, filter, wash with deionized water three times, and dry in an oven at 70°C for 10 minutes to obtain solid particles.
[0043] Among them, the carboxyl and amino groups contained in betaine can react with the hydroxyl groups on the surface of calcium carbonate through electrostatic adsorption, so that the betaine is coated on the surface of nano-calcium carbonate, avoiding the high hardness of nano-calcium carbonate and causing the rupture of the swelling tape.
[0044] Furthermore, the dosage ratio of betaine, nano-calcium carbonate and ethanol is (1-2) g: (0.2-0.4) g: (15-25) mL.
[0045] A2. Add acrylamide and methyl acryloylethyl sulfobetaine to deionized water, stir evenly, add solid particles and a 0.01 mol / L potassium persulfate aqueous solution, stir for 15 minutes to remove bubbles in the solution, react at 60°C for 2.5 hours to obtain a composite hydrogel.
[0046] Among them, potassium persulfate aqueous solution is used as a catalyst to make acrylamide and methacryloylethyl sulfobetaine copolymerize, and the chains of acrylamide and methacryloylethyl sulfobetaine are entangled with each other to form a three-dimensional network structure. Betaine-modified nano-calcium carbonate can also form a flexible hydrogel through ion cross-linking with acrylamide and methacryloylethyl sulfobetaine in the cross-linked network structure, which is filled into the pressure-sensitive adhesive as a pressure-sensitive layer to improve the flexibility of the swollen tape.
[0047] Furthermore, the usage ratio of acrylamide, methacryloylethyl sulfobetaine, deionized water, solid particles, and potassium persulfate aqueous solution is (2.1-2.5) g: (1.6-2) g: (25-35) mL: (1-2) g: (1-3) mL.
[0048] Furthermore, the weight percentages of the release layer raw materials are as follows: 80-90 parts of diluent and 10-20 parts of silicone oil prepolymer.
[0049] Furthermore, the diluent is selected from ethyl acetate or toluene.
[0050] Further, the silicone oil prepolymer is specifically prepared by the following steps:
[0051] Isophorone diisocyanate, alkylhydroxy silicone oil and amino silicone oil were mixed, stirred at 40°C for 20 minutes, polyethylene glycol was added, stirred and reacted for 10 minutes, the temperature was raised to 65°C, β-hydroxyethyl acrylate was added, the reaction was continued for 30 minutes, and the mixture was cooled to room temperature to obtain a silicone oil prepolymer.
[0052] Furthermore, the mass ratio of isophorone diisocyanate, alkylhydroxy silicone oil, amino silicone oil, polyethylene glycol, and β-hydroxyethyl acrylate is (15-25) g: (6-7) g: (3-4) g: (2-2.2) g: (1-2) g.
[0053] Furthermore, compared with the prior art, the present invention has the following beneficial effects:
[0054] (1) In the technical solution of the present invention, in the expanded substrate, titanium carbide nanosheets are two-dimensional layered nanosheets with small band gap, excellent mechanical strength, large specific surface area and interlayer spacing, and rich chemical surface. Porous carbon is synthesized on the surface of the titanium carbide nanosheets. The synthesized porous carbon provides more ion storage capacity and transmission channels, so that the expanded substrate is coated on the lithium-ion battery electrode, and has a high lithium ion transmission efficiency, thereby not affecting the electrochemical performance of the lithium-ion battery. In addition, the porous carbon has good polar strength and is filled into the expanded substrate, thereby improving the compressive resistance of the swelling tape.
[0055] (2) In the technical solution of the present invention, the expansion substrate also contains modified acrylate monomers; the acrylate monomers are grafted onto the polysaccharide molecular chain to provide a photopolymerizable monomer, so that the modified acrylate monomers and the polyurethane resin are photo-initiated to polymerize to form an expansion substrate with a three-dimensional network structure. The polysaccharide molecular chain contains a large number of polar functional groups such as hydroxyl groups and ester groups. The polar functional groups are easy to absorb the ester solvent in the electrolyte, so that a large amount of ester solvents enter the three-dimensional network structure of the expansion substrate, and the substrate can expand at a high rate. In addition, the acrylate monomer grafted onto the polysaccharide initiates copolymerization under light, has excellent stability, can reduce side reactions with the electrolyte, reduce the self-discharge rate of the battery and improve the cycle stability.
[0056] (3) In the technical scheme of the present invention, in the expansion substrate, the hydroxyl group in the grape polyphenol can react with the isocyanate of trimethylhexamethylene diisocyanate to combine with an amide bond, thereby increasing the adhesion performance with the pole piece. The formed composite contains hydroxyl, isocyanate and amide bonds, which can be combined with the composite titanium carbide nanosheets through chemical bonds, so that the composite is grafted on the surface of the composite titanium carbide nanosheets. The hydroxyl and isocyanate carried by the composite can undergo a cross-linking reaction with the carboxyl and hydroxyl groups in the polar expansion substrate, so that the composite titanium carbide nanosheet polar expansion substrate, on the one hand, improves the transmission efficiency of the lithium-ion battery and improves the electrochemical performance. On the other hand, the small size effect of the composite titanium carbide nanosheet can also fill the gap between the lithium battery cell and the outer shell, so that the outer shell and the inner core of the lithium battery are connected as one. In addition, the composite titanium carbide nanosheet increases the cross-linking density of the polar expansion substrate, thereby improving the mechanical strength of the polar expansion substrate.
[0057] (4) In the technical solution of the present invention, in the pressure-sensitive layer, nano calcium carbonate is added as a filler to the pressure-sensitive adhesive. As a pressure-sensitive layer, it can improve the high temperature resistance and corrosion resistance of the swelling tape; the carboxyl and amino groups contained in betaine can react with the hydroxyl groups on the surface of calcium carbonate through electrostatic adsorption, so that betaine is coated on the surface of nano calcium carbonate, avoiding the high hardness of nano calcium carbonate, which leads to the rupture of the swelling tape. Acrylamide and methyl acryloylethyl sulfonyl betaine and betaine-modified nano calcium carbonate form a flexible hydrogel, which is filled into the pressure-sensitive adhesive. As a pressure-sensitive layer, it can improve the flexibility of the swelling tape, and improve the dispersibility of calcium carbonate powder in the pressure-sensitive adhesive system, promote the compactness of acrylic pressure-sensitive adhesive, thereby improving the adhesion between acrylic pressure-sensitive adhesive and the surface of lithium-ion battery pole piece, and further improving the adhesion.
[0058] (5) In the technical solution of the present invention, the release layer is composed of a diluent and a silicone oil prepolymer, and is coated on the outer surface of the expanded substrate to form a release layer, which can reduce the unwinding force of the finished tape and also allow the tape to be rolled up smoothly during production to avoid wrinkles. DETAILED DESCRIPTION
[0059] The technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0060] The raw materials used in the embodiments of the present invention are as follows: titanium carbide nanosheets (Xi'an Qiyue Biotechnology Co., Ltd., titanium carbide nanosheets with a diameter of 0.1-1 μm and a thickness of 20-40 nm); aromatic polyurethane acrylate polymer (model CN9782, purchased from Guangzhou Jingyi New Materials Co., Ltd.); acrylic acid (model 79-10-7, purchased from Jinan Jiao Chemical Co., Ltd.); isooctyl acrylate (model 103-11-7, purchased from Jiangsu Minglin Chemical Technology Co., Ltd.); methacrylate laurate (model 142-90-5, purchased from Jinan Century Tongda Chemical Co., Ltd.); toluene (model 108-88-3, purchased from Guangdong Xiaoda Chemical Co., Ltd.).
[0061] Dextran (molecular weight 40KDa, purchased from Shanghai Jianglai Biotechnology Co., Ltd.); grape polyphenol (content 50-70%, purchased from Nanjing Dasifu Biotechnology Co., Ltd.); hydroxyethyl methacrylate (analytical grade, Tianjin Xiensi Biochemical Technology Co., Ltd.); oxalic acid (purity 99.6%, Jiangsu Minglin Chemical Technology Co., Ltd.); betaine (purity 99%, Wuhan Kemik Biomedical Technology Co., Ltd.); methacryloylethyl sulfobetaine (analytical grade, Aladdin Reagent); acrylamide (analytical grade, Maclean); polyethylene glycol (purity 98%, Shandong Jinyueyuan New Materials Co., Ltd.); isophorone diisocyanate, trimethylhexamethylene diisocyanate (chemically pure, Qingdao Xinyutian Chemical Import Company); amino silicone oil, alkylhydroxy silicone oil (chemically pure, Shandong Dayi Chemical Co., Ltd.); β-hydroxyethyl acrylate (polymerization grade, Beijing Oriental Chemical Plant).
[0062] The silicone oil prepolymer is specifically prepared by the following steps:
[0063] Mix 20g of isophorone diisocyanate, 6.5g of alkylhydroxy silicone oil and 3.5g of amino silicone oil, stir at 40°C for 20min, add 2.1g of polyethylene glycol, stir and react for 10min, heat to 65°C, add 1.5g of β-hydroxyethyl acrylate, continue to react for 30min, cool to room temperature to obtain a silicone oil prepolymer.
[0064] Example 1
[0065] The reinforcing filler is specifically prepared by the following steps:
[0066] A1. Add 0.2g titanium carbide nanosheets and 5g glucose to 50mL deionized water, stir evenly, add 5.2g oxalic acid and 0.5mL hydrochloric acid with a mass fraction of 36%, stir and react at 70°C for 30min, filter, wash and dry, place in a tube furnace, add 5mL potassium hydroxide, activate at 400°C for 1h, introduce nitrogen, calcine at 850°C for 3.5h, cool to room temperature, take out, wash 3 times with deionized water, and dry in an oven at 70°C for 10min to obtain composite titanium carbide nanosheets.
[0067] A2. Add 2.5 g of grape polyphenols and 1.5 g of trimethylhexamethylene diisocyanate to 15 mL of dimethyl sulfoxide, stir evenly, add 0.02 g of triethylamine, stir at 60 ° C for 30 min, add 0.5 g of composite titanium carbide nanosheets, stir and react for 10 min, filter, wash with deionized water 3 times, and dry in an oven at 70 ° C for 10 min to obtain a reinforced filler.
[0068] Comparative Example 1
[0069] The difference between this comparative example and Example 1 is that the composite titanium carbide nanosheets are replaced by titanium carbide nanosheets, and the remaining steps and raw materials are the same as Example 1.
[0070] Add 2.5 g of grape polyphenol and 1.5 g of trimethylhexamethylene diisocyanate to 15 mL of dimethyl sulfoxide, stir evenly, add 0.02 g of triethylamine, stir at 60 ° C for 30 min, add 0.5 g of titanium carbide nanosheets, stir and react for 10 min, filter, wash with deionized water 3 times, and dry in an oven at 70 ° C for 10 min to obtain a reinforced filler.
[0071] Comparative Example 2
[0072] The difference between this comparative example and Example 1 is that grape polyphenol and trimethyl hexamethylene diisocyanate are not added, and the remaining steps and raw materials are the same as those in Example 1.
[0073] 0.2 g of titanium carbide nanosheets and 5 g of glucose were added to 50 mL of deionized water, stirred evenly, 5.2 g of oxalic acid and 0.5 mL of 36% hydrochloric acid were added, and the mixture was stirred and reacted at 70°C for 30 min. After filtering, washing and drying, the mixture was placed in a tube furnace, 5 mL of potassium hydroxide was added, and the mixture was activated at 400°C for 1 h. Nitrogen was introduced, and the mixture was calcined at 850°C for 3.5 h. The mixture was cooled to room temperature, taken out, washed with deionized water for 3 times, and dried in an oven at 70°C for 10 min to obtain a reinforced filler.
[0074] Example 2
[0075] The modified acrylic ester monomer is specifically prepared by the following steps:
[0076] Add 1.3 g of hydroxyethyl methacrylate and 4 g of dextran to 50 mL of ethanol, stir evenly, place in a 50°C water bath, add 0.5 mL of 36% hydrochloric acid aqueous solution, stir and react for 30 minutes, take out, cool to room temperature, stand for 2 hours, remove the upper ethanol solution, remove the reactant, place in a 60°C oven and dry for 10 minutes, grind into powder to obtain a modified acrylic ester monomer.
[0077] Example 3
[0078] The composite hydrogel is specifically prepared by the following steps:
[0079] B1. Add 1.5 g of betaine and 0.3 g of nano-calcium carbonate to 20 mL of ethanol, stir at 40°C for 30 min, filter, wash with deionized water three times, and dry in an oven at 70°C for 10 min to obtain solid particles.
[0080] B2. Add 2.3 g acrylamide and 1.8 g methacryloylethyl sulfobetaine to 30 mL of deionized water, stir evenly, add 1.5 g of solid particles and 2 mL of 0.01 mol / L potassium persulfate aqueous solution, stir for 15 min to remove bubbles in the solution, react at 60 ° C for 2.5 h to obtain a composite hydrogel.
[0081] Comparative Example 3
[0082] The difference between this comparative example and Example 3 is that the solid particles are replaced by nano-calcium carbonate, and the remaining steps are synchronized with Example 3.
[0083] 2.3 g acrylamide and 1.8 g methacryloylethyl sulfobetaine were added to 30 mL deionized water and stirred evenly. 1.5 g nano-calcium carbonate and 2 mL 0.01 mol / L potassium persulfate aqueous solution were added and stirred for 15 min to remove bubbles in the solution. The mixture was reacted at 60 °C for 2.5 h to obtain a composite hydrogel.
[0084] Example 4
[0085] A method for preparing a novel swelling tape for lithium batteries comprises the following steps:
[0086] S1. Mix 40 parts of aromatic polyurethane acrylate polymer, 30 parts of modified acrylate monomer, 5 parts of reinforcing filler and 0.1 parts of (2,4,6-trimethylbenzoyl) diphenylphosphine oxide, melt-blend at 80°C to obtain a melt, and photo-cure the melt by ultraviolet light to obtain an expanded substrate, wherein the ultraviolet light irradiation power is 250 W, the wavelength is 250 nm, the temperature is 25°C, and the irradiation time is 13 min.
[0087] S2. Mix 50 parts of acrylic acid, 10 parts of isooctyl acrylate, 6 parts of lauric methacrylate, 2 parts of composite hydrogel, 0.2 parts of toluene diisocyanate, 0.1 parts of azobisisobutyronitrile, and 50 parts of toluene, stir evenly, apply it on the lower surface of the expandable substrate using a scraper coater, and obtain an expandable substrate with a pressure-sensitive adhesive layer through thermal curing, wherein the thermal curing temperature is 110°C and the thermal curing time is 2.5 min.
[0088] S3. Mix 90 parts of toluene and 20 parts of silicone oil prepolymer, apply it on the upper surface of the expansion substrate with a pressure-sensitive adhesive layer using a micro-concave applicator, heat and cure it at 140°C for 1.5 minutes, and then roll it up to obtain an expansion substrate with a release layer and a pressure-sensitive adhesive layer, i.e., a new swelling tape for lithium batteries, wherein the new swelling tape for lithium batteries includes a pressure-sensitive adhesive layer, an expansion substrate layer, and a release layer from the inside to the outside; the pressure-sensitive adhesive layer has a thickness of 8um, the expansion substrate layer has a thickness of 45um, and the release layer has a thickness of 1.5um.
[0089] Example 5
[0090] A method for preparing a novel swelling tape for lithium batteries comprises the following steps:
[0091] S1. 60 parts of polyurethane acrylate polymer, 50 parts of modified acrylate monomer, 5.5 parts of reinforcing filler and 0.5 parts of 1-hydroxycyclohexyl phenyl ketone are mixed, melt-blended at 80°C to obtain a melt, and the melt is photocured by ultraviolet light to obtain an expanded substrate, wherein the ultraviolet light irradiation power is 250 W, the wavelength is 250 nm, the temperature is 25°C, and the irradiation time is 13 min.
[0092] S2. Mix 55 parts of acrylic acid, 13 parts of isooctyl acrylate, 8 parts of lauric methacrylate, 4 parts of composite hydrogel, 0.6 parts of toluene diisocyanate, 0.3 parts of benzoyl peroxide, and 60 parts of toluene, stir evenly, apply it on the lower surface of the expandable substrate using a scraper coater, and obtain an expandable substrate with a pressure-sensitive adhesive layer through thermal curing, wherein the thermal curing temperature is 110°C and the thermal curing time is 2.5 min.
[0093] S3. Mix 85 parts of ethyl acetate and 15 parts of silicone oil prepolymer, apply them on the upper surface of the expansion substrate with a pressure-sensitive adhesive layer using a micro-concave applicator, heat and cure at 140°C for 1.5 minutes, and then roll up to obtain an expansion substrate with a release layer and a pressure-sensitive adhesive layer, i.e., a new swelling tape for lithium batteries, wherein the new swelling tape for lithium batteries includes a pressure-sensitive adhesive layer, an expansion substrate layer, and a release layer from the inside to the outside; the pressure-sensitive adhesive layer has a thickness of 8um, the expansion substrate layer has a thickness of 45um, and the release layer has a thickness of 1.5um.
[0094] Example 6
[0095] A method for preparing a novel swelling tape for lithium batteries comprises the following steps:
[0096] S1. Mix 70 parts of aromatic polyurethane acrylate polymer, 60 parts of modified acrylate monomer, 6 parts of reinforcing filler and 1 part of 2-hydroxy-2-methyl-1-phenyl-1-propanone, melt-blend them at 80°C to obtain a melt, and photo-cure the melt by ultraviolet light to obtain an expanded substrate, wherein the ultraviolet light irradiation power is 250 W, the wavelength is 250 nm, the temperature is 25°C, and the irradiation time is 13 min.
[0097] S2. Mix 60 parts of acrylic acid, 15 parts of isooctyl acrylate, 10 parts of lauric methacrylate, 5 parts of composite hydrogel, 1 part of toluene diisocyanate, 0.5 parts of benzoyl peroxide, and 70 parts of toluene, stir evenly, apply it on the lower surface of the expandable substrate using a scraper coater, and obtain an expandable substrate with a pressure-sensitive adhesive layer through thermal curing, wherein the thermal curing temperature is 110°C and the thermal curing time is 2.5 min.
[0098] S3. Mix 90 parts of ethyl acetate and 20 parts of silicone oil prepolymer, apply them on the upper surface of the expansion substrate having a pressure-sensitive adhesive layer using a micro-concave applicator, heat and cure at 140°C for 1.5 minutes, and then roll up to obtain an expansion substrate with a release layer and a pressure-sensitive adhesive layer, i.e., a new swelling tape for lithium batteries, wherein the new swelling tape for lithium batteries comprises, from inside to outside, a pressure-sensitive adhesive layer, an expansion substrate layer, and a release layer; the pressure-sensitive adhesive layer has a thickness of 8um, the expansion substrate layer has a thickness of 45um, and the release layer has a thickness of 1.5um.
[0099] Comparative Example 4
[0100] The difference between this comparative example and Example 5 is that the reinforcing filler prepared in Example 5 is replaced by the material prepared in Comparative Example 1, and the remaining steps are synchronized with Example 5.
[0101] Comparative Example 5
[0102] The difference between this comparative example and Example 5 is that the material prepared in Example 5 is replaced by the material prepared in Comparative Example 2, and the remaining steps are synchronized with Example 5.
[0103] Comparative Example 6
[0104] The difference between this comparative example and Example 5 is that the modified acrylic ester monomer is replaced by hydroxyethyl methacrylate, and the remaining steps are synchronized with Example 5.
[0105] Comparative Example 7
[0106] The difference between this comparative example and Example 5 is that the composite hydrogel prepared in Example 5 is replaced by the material prepared in Comparative Example 3, and the remaining steps are synchronized with Example 5.
[0107] The performance of the novel swelling tape for lithium batteries prepared in Examples 4-6 and Comparative Examples 4-7 is now tested;
[0108] The new lithium battery prepared above was cut into samples with a length of 55 mm and a width of 58 mm using swelling tape, and immersed in an electrolyte at 85°C for 4 hours to observe its swelling and shape retention. The electrolyte included lithium hexafluorophosphate and ethylene carbonate in a ratio of 1:3. The test was carried out at a current density of 200 mA / g, and the first discharge capacity was recorded.
[0109] Swelling ratio in the longitudinal direction = (length after immersion in electrolyte / 55) × 100%.
[0110] Thickness direction swelling ratio = (width after immersion in electrolyte / 58) x 100%.
[0111] High temperature resistance: stick the tape on the stainless steel plate, bake it in a constant temperature oven at 150℃ for 2.5h, then peel off the tape in the oven (hot peeling), and observe whether there is any trace of residual glue on the stainless steel plate. If there is, the high temperature resistance is poor, and if there is no, the high temperature resistance is good. Peel strength: according to GB / T2792-2014 standard, use a peel force tester to measure (peeling rate is 300mm / min).
[0112] The new lithium battery swelling tape prepared above was subjected to low-load tension and compression test and low-frequency tension and compression cycle test. The size of the swelling tape was 45×15×2mm (length×width×thickness), and the rate was 50mm / min. The strain size of the tension and compression cycle test was 800%, the number of cycles was 10, and the tensile strength was calculated. The test results are shown in Table 1 below.
[0113] Table 1: Performance Test
[0114]
[0115] It can be seen from the data in Table 1 that in Comparative Example 4, the composite titanium carbide nanosheets are replaced with a reinforcing filler prepared from titanium carbide nanosheets for the preparation of the swelling tape, and its mechanical properties and electrochemical properties are reduced. This may be because porous carbon is synthesized on the surface of the titanium carbide nanosheets. The synthesized porous carbon provides more ion storage capacity and transmission channels, so that the expansion substrate is coated on the lithium ion battery pole piece, and has a higher lithium ion transmission efficiency, thereby not affecting the electrochemical properties of the lithium ion battery. In addition, the porous carbon has good polarity strength, which is filled into the expansion substrate to improve the compressive strength of the swelling tape; in Comparative Example 5, no reinforcing filler prepared by adding grape polyphenol and trimethyl hexamethylene diisocyanate is used to prepare the swelling tape, and its mechanical properties and electrochemical properties are reduced. This may be because the isocyanate reaction of hexamethylene diisocyanate is combined with an amide bond, which increases the adhesion to the pole piece, and the hydroxyl and isocyanate carried can be combined with the polar expansion substrate. The carboxyl and hydroxyl groups undergo a cross-linking reaction, so that the transmission efficiency of the lithium ion battery and the electrochemical performance are improved in the polar expansion substrate of the composite titanium carbide nanosheets; in Comparative Example 6, the expansion substrate prepared by replacing the modified acrylic ester monomer with hydroxyethyl methacrylate is used to prepare the swelling tape, and its swelling ratio and peel strength decrease. This may be because the modified acrylic ester monomer and the polyurethane resin are photoinitiated to polymerize, and the polysaccharide molecular chain contains a large number of polar functional groups such as hydroxyl groups and ester groups. The polar functional groups are easy to absorb the ester solvent in the electrolyte, so that a large amount of it enters the three-dimensional network structure of the expansion substrate, and the substrate is able to expand at a higher rate; in Comparative Example 7, the solid particles are replaced by the expansion substrate prepared by nano-calcium carbonate. The expansion tape is used to prepare the swelling tape, and its peel strength decreases. This may be because the carboxyl and amino groups contained in betaine can react with the hydroxyl groups on the surface of calcium carbonate through electrostatic adsorption, thereby avoiding the high hardness of the nano-calcium carbonate and causing the swelling tape to rupture.
[0116] The data in Table 1 show that the new swelling tape for lithium batteries prepared in Examples 3-5 not only has good swelling ratio and adhesion, but also has good flexibility. The substrate raw materials are melt blended, and then photocured by ultraviolet light irradiation to obtain an expanded substrate. The pressure-sensitive adhesive layer raw materials are mixed, coated on the lower surface of the expanded substrate, and thermally cured to obtain an expanded substrate with a pressure-sensitive adhesive layer. The release layer raw materials are mixed, and the release layer mixture is coated on the upper surface of the expanded substrate with a pressure-sensitive adhesive layer, heated and cured, and rolled to obtain an expanded substrate with a release layer and a pressure-sensitive adhesive layer, that is, the new swelling tape for lithium batteries meets the test performance requirements, while the new swelling tape for lithium batteries of Comparative Examples 5-8 does not meet the performance requirements, indicating that the new swelling tape for lithium batteries prepared by the present invention not only has a good swelling ratio and adhesion, but also has good flexibility.
[0117] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0118] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A method for preparing a novel swelling tape for lithium batteries, characterized in that: The following steps are involved: S1. The substrate raw materials are melt-blended and then photocured by ultraviolet light to obtain an expanded substrate; S2. The pressure-sensitive adhesive layer raw materials are mixed, coated on the lower surface of the expansion substrate, and thermally cured to obtain an expansion substrate having a pressure-sensitive adhesive layer; S3. Mix the release layer raw materials, apply the release layer mixture on the upper surface of the expansion substrate with the pressure-sensitive adhesive layer, heat and cure, and roll up to obtain an expansion substrate with a release layer and a pressure-sensitive adhesive layer, that is, a new swelling tape for lithium batteries.
2. The method for preparing a novel swelling tape for lithium batteries according to claim 1, characterized in that: The mass percentages of the substrate raw materials are as follows: 40-70 parts of polyurethane resin, 30-60 parts of modified acrylate monomers, 5-6 parts of reinforcing fillers, and 0.1-1 parts of photoinitiator.
3. The method for preparing a novel swelling tape for lithium batteries according to claim 2, characterized in that: The reinforcing filler is prepared by reacting grape polyphenol with trimethyl hexamethylene diisocyanate and then mixing with composite titanium carbide nanosheets; The composite titanium carbide nanosheets are prepared by modifying the surface of titanium carbide nanosheets with oxalic acid, mixing with an organic precursor, and calcining at a high temperature; The modified acrylate monomer is prepared by reacting dextran with an acrylate monomer; The acrylic acid ester monomer is selected from any one of hydroxyethyl methacrylate, hydroxyethyl acrylate and acrylic acid.
4. The method for preparing a novel swelling tape for lithium batteries according to claim 2, characterized in that: The photoinitiator is selected from any one of (2,4,6-trimethylbenzoyl)diphenylphosphine oxide, 1-hydroxycyclohexyl phenyl ketone, and 2-hydroxy-2-methyl-1-phenyl-1-propanone; and the polyurethane resin is selected from polyurethane acrylate polymers or aromatic polyurethane acrylate polymers.
5. The method for preparing a novel swelling tape for lithium batteries according to claim 1, characterized in that: The weight percentages of the raw materials for the pressure-sensitive adhesive layer are: 50-60 parts of acrylic acid, 10-15 parts of isooctyl acrylate, 6-10 parts of methacrylate laurate, 2-5 parts of composite hydrogel, 0.2-1 parts of curing agent, 0.1-0.5 parts of initiator, and 50-70 parts of toluene.
6. The method for preparing a novel swelling tape for lithium batteries according to claim 5, characterized in that: The composite hydrogel is prepared by modifying the surface of nano-calcium carbonate with betaine, and then mixing with acrylamide and methacryloylethyl sulfobetaine, and stirring for reaction; The particle size of the nano calcium carbonate is 10-13 μm.
7. The method for preparing a novel swelling tape for lithium battery according to claim 5, characterized in that: The curing agent is selected from toluene diisocyanate; the initiator is selected from benzoyl peroxide or azobisisobutyronitrile.
8. The method for preparing a novel swelling tape for lithium batteries according to claim 1, characterized in that: The mass percentages of the release layer raw materials are: 80-90 parts of diluent and 10-20 parts of silicone oil prepolymer; The diluent is selected from ethyl acetate or toluene.
9. The method for preparing a novel swelling tape for lithium battery according to claim 1, characterized in that: The novel swelling tape for lithium battery comprises a pressure-sensitive adhesive layer, an expansion substrate layer and a release layer from inside to outside; the thickness of the pressure-sensitive adhesive layer is 6-10um, the thickness of the expansion substrate layer is 40-50um, and the thickness of the release layer is 1-2um.
10. A novel swelling tape for lithium battery prepared by the preparation method according to any one of claims 1 to 9.